The effects of government agencies and industry-initiated interventions in the loomweaving industry in Miagao, Iloilo 1995-2000. - Cabrera, Genebeth A.
The study aims to determine the effects of the government agencies/industry-initiated interventions to the loom weaving firms/industry in Miag-ao: 1995-2000. Indept interview with the respondents was done based on the five areas of business development: organization/management, managerial, techno-production, marketing and financial, to determine the effect of the government agencies/industry-initiated interventions to the loom weaving firms/industry., Several activities were conducted to the loom weaving firms/industry based on their needs as determined in the Training Need Assessment Seminar/Workshop conducted by the Department of Trade and Industry and other assisting agencies. Firms successfully learned from the training/seminars and consultancies conducted to them; however, applications were limited because of the lack of resources. The absorptive capacity of the firm owners/weavers was also a problem that is why their learning from the training/seminar and consultancies showed limited applications. There exist the Katilingban sang Manughabol sa Iloilo of which some firms were members, but industry-initiated interventions were limited. Financial assistance from the private entities through the association was availed by the firms. Increased in sales, income, employment and investment was gained by the firms/industry as shown in the records and reports made by the agencies assisting them for the last five years (1995-2000).